Efektifitas Uji Kompetensi Berbasis Web terhadap Peningkatan Kepercayaan Diri Mahasiswa - Andi Wilda Arianggara; Norma Jeepi Margiyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Competency tests organized by universities in collaboration with professional organizations, health care training institutions become a requirement for vocational and professional education graduation. Based on the results of the 2019 competency test, 19.66% of competency test participants were declared competent which means it is still far from the expected target. This research aims to find out the effectiveness of web-based competency test models against increasing the confidence of midwifery students in the face of competency tests. The method used in this study is the Pre-Experimental One Group Pretest-Posttest. The study was conducted at Politeknik Kesehatan Kementerian Kesehatan Makassar and Universitas Megarezky.Sampling is done with the Purposive Sampling Technique which is as many as 45 samples. Data is analyzed using statistical analysis, namely byconducting a data normality test and then followed by the Wilcoxon Sign Rank Test. The effectiveness of using a web-based competency test model found that the average level of confidence of students before the intervention was 78% in the high confidence category and the average confidence of students after the intervention was 84% in the category of very high trust. Based on the analysis of pretest and posttest results there is an increase in student confidence before and after the intervention. Furthermore, the Wilcoxon Test has obtained a p-value of 0.00 < 0.05 which means there is asignificant difference between the pretest and posttest grades of students so that the web-based competency test model is effective in increasing theconfidence of students facing competency tests